Sinnott-Armstrong's Empirical Challenge to Moral Intuitionism: a Novel Critique - Hermann, Julia (Ethical theory and moral practice, 2017)
This paper provides a novel critique of Walter Sinnott-Armstrong's influential argument against epistemological moral intuitionism, the view that some people are non-inferentially justified in believing some moral propositions. At the beginning of the twenty-first century, this view experienced a revival, which coincided with an increasing interest in empirical research on intuitions. The results of that research are seen by some as casting serious doubt on the reliability of our moral intuitions. According to Sinnott-Armstrong, empirical evidence shows that our moral beliefs have a high error rate in general, which creates a need for inferential confirmation for every single moral belief. His argument involves the problematic assumption that it is reasonable for informed moral believers to ascribe a high probability of error to every particular moral belief unless the believer has some special evidence that this particular moral belief belongs to a class that has a lower probability of error than the class of moral beliefs (ERROR). Focussing on the non-moral example that Sinnott-Armstrong uses in the latest reformulation of his argument, the Californian wine example, I argue that (i) apart from exceptional circumstances, the description of moral agents as ascribing correctness probabilities to their moral beliefs is odd, (ii) ERROR reveals an awkward picture of how agents relate to their moral beliefs and (iii) ERROR is problematic from the perspective of moral competence. This critique goes deeper than the worries raised by other critics to earlier versions of the argument, and part of it applies to moral intuitionism as well.